Allah adalah Perisai: Studi Penelitian Puitis-Afektif Mazmur 3 - Armand Barus (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Abstract. This article attempts to enrich the varieties of reading methods of psalm. The enrichment is conducted using an approach called poetic-affective criticism. Poetic-affective criticism is a method of reading a lament psalm by seriously paying attention to the elements in lament psalms, such as major characteristics of Hebrew poetry, lament, feeling, the concept of God, and mood. Applying poetic-affective criticism to Psalm 3 produces different meaning from that was suggested by most scholars. By this study it was revealed that psalmist succeeds in dealing with physical and verbal assaults against the psalmist because God is a shield of the psalmist. In and through the suffering, the psalmist is able to know God as a shield that protects the psalmist.Abstrak. Artikel ini merupakan suatu upaya untuk memperkaya keragaman metode penafsiran mazmur. Pengayaan itu dilakukan dengan memakai suatu pendekatan penelitian puitis-afektif (poetic-affective criticism). Penelitian puitis-afektif adalah metode pembacaan mazmur ratapan dengan memperhatikan unsur-unsur terkandung dalam mazmur ratapan seperti karakteristik utama puisi Ibrani, yaitu keluhan, perasaan, konsep Allah dan perubahan suasana teks (mood). Penerapan penelitian puitis-afektif terhadap Mazmur 3 dapat menghasilkan pemaknaan berbeda dengan tafsiran kebanyakan penafsir. Dalam hal ini terungkap pemazmur berhasil menghadapi serangan fisik dan perkataan terhadap dirinya karena Allah adalah perisainya. Melalui dan di dalam penderitaannya pemazmur mengenal Allah sebagai perisai yang melindunginya.